2012
DOI: 10.1016/j.autneu.2012.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of the insular cortex gyri to autonomic challenges

Abstract: Determining insular functional topography is essential for assessing autonomic consequences of neural injury. We examined that topography in the five major insular cortex gyri to three autonomic challenges, the Valsalva, hand grip, and foot cold pressor, using functional magnetic resonance imaging (fMRI) procedures. Fifty-seven healthy subjects (age±std: 47±9 years) performed four 18 s Valsalva maneuvers (30 mmHg load pressure), four hand grip challenges (16 s at 80% effort), and a foot cold pressor (60 s, 4°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 47 publications
12
97
1
Order By: Relevance
“…Previous neuroimaging studies have shown that the insula is activated during physiological manouevres that increase MSNA, including the Valsalva manoeuvre (Henderson et al, 2002;Macey et al, 2012)), inspiratorycapacity apnoea , cold-pressor test (Harper et al, 2003;Macey et al, 2012), hand-grip exercise (Wong et al, 2007a(Wong et al, , 2007bSander et al, 2010;Macey et al, 2012) and lower-body negative pressure (Kimmerly et al, 2005). Moreover, there is evidence for regional specialization of the insula for different autonomic challenges (Macey et al, 2012). It is known from work in experimental animals that the insula does not project directly to the RVLM but does project to the lateral posterior hypothalamus (Cechetto and Chen, 1990), so may mediate its cardiovascular effects via indirect projections to the hypothalamus.…”
Section: Cortical and Subcortical Changes During Exercise And Post-exmentioning
confidence: 97%
“…Previous neuroimaging studies have shown that the insula is activated during physiological manouevres that increase MSNA, including the Valsalva manoeuvre (Henderson et al, 2002;Macey et al, 2012)), inspiratorycapacity apnoea , cold-pressor test (Harper et al, 2003;Macey et al, 2012), hand-grip exercise (Wong et al, 2007a(Wong et al, , 2007bSander et al, 2010;Macey et al, 2012) and lower-body negative pressure (Kimmerly et al, 2005). Moreover, there is evidence for regional specialization of the insula for different autonomic challenges (Macey et al, 2012). It is known from work in experimental animals that the insula does not project directly to the RVLM but does project to the lateral posterior hypothalamus (Cechetto and Chen, 1990), so may mediate its cardiovascular effects via indirect projections to the hypothalamus.…”
Section: Cortical and Subcortical Changes During Exercise And Post-exmentioning
confidence: 97%
“…In addition, the anterior and posterior regions of the insular cortex were shown to have different roles. The findings from a previous study on the insular cortex using 3 examinations of the autonomic function (Valsalva maneuvers, 4 hand grip challenges, and a foot cold pressor) with functional MRI indicated that the right anterior insular cortex was associated with sympathetic activity [9]. A study examining the effects of the location of acute ischemic stroke including the insular cortex on the levels of troponin and their relative temporal changes demonstrated a prominent role of the right dorsal anterior insular cortex in the parasympathetic control of cardiac and autonomic functions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the lateralization as well as the anteroposterior representation of insular regulation may partially depend on the nature of the eliciting stimulus (128,198). Using three different stimuli (Valsalva maneuver, right hand grip, and cold pressor challenge), fMRI responses were correlated with respect to insular location.…”
Section: Human Functional Studiesmentioning
confidence: 99%